DESENVOLVIMENTO E IMPLANTAÇÃO DE SALA DE SITUAÇÃO EM UNIDADE DE ACIDENTE VASCULAR CEREBRAL - Geyson Pereira Santana (2023)
Stroke is one of the leading causes of death worldwide, affecting approximately 15 million people per year. Stroke is a condition that results from a vascular injury to the Central Nervous System (CNS) and is classified as a neurological impairment or dysfunction. Monitoring indicators of this disease is crucial to support decision-making, and one tool that can assist in this regard is the Health Situation Room (HSS), which enables the monitoring of information to support clinical and management decision-making. The HSS is a virtual environment that provides a set of data organized into spreadsheets or systems, where information can be obtained and indicators monitored, characterizing, measuring, and explaining the health-disease profile of a population, including health issues, as well as their determinants. With the aim of ensuring compliance with the guidelines set by the Ministry of Health, particularly government decree 665 of April 12, 2012, in a Stroke Care Unit (SCU) at the University Hospital (UH) in Campo Grande/MS, this study developed and implemented the HSS within this public hospital sector. The research unfolded in stages, including requirements gathering, use case modeling, low-code platform selection, profile definition, HSS dashboard design, and the production of the final prototype. The results demonstrated that the system evaluation was well-received by the healthcare team, with an average rating of 4.83 after system implementation. It provided standardized data entry forms, connectivity to the UH's hospital information system for patient searches, patient registration over a specific period, and the availability of the HSS dashboard. This work successfully developed and implemented an HSS in a public hospital, with the potential for adoption by other healthcare units that cater to stroke patients.